The impact of feed additives to improve growth performance in nursery pigs and meat goats - Dahmer, Payton Lane (Kansas State University, 2020)
Four studies were conducted to evaluate methods to nutritionally improve nursery pig or meat goat growth and efficiency. In Exp. 1, a total of 360 weanling pigs (DNA 200 x 400; 5.4 ± 0.07 kg BW) were fed for 35 days, with 6 pigs/pen and 10 replicate pens/treatment. Pigs were allotted based on BW in a completely randomized design to treatment diets: 1) Negative control; 2) Control + 3,000 ppm ZnO in phase 1 and 2,000 ppm ZnO in phase 2; 3) Control + 50 g/ton carbadox; 4) Control + C6:C8:C10 MCFA blend; 5) Control + Proprietary Oil Blend (Feed Energy Corp.); 6) Control + monolaurate blend (FORMI GML from ADDCON). Treatments were fed through two dietary phases and a common diet fed through phase three. Pigs and feeders were individually weighed on a weekly basis to determine average daily gain (ADG) and average daily feed intake (ADFI). From d 0 to 19, pigs being fed the ZnO or Carbadox diets had the greatest ADG. These pigs had significantly higher (P < 0.05) ADG than pigs fed the control or Feed Energy Proprietary Oil Blend, while pigs fed the C6:C8:C10 blend or FORMI GML diets had similar (P > 0.05) ADG compared to those fed carbadox. Overall, these results show that ZnO and carbadox are valuable additives to help maximize growth performance in early stages of the nursery. Some MCFA products may result in similar performance while others restrict it. Next, a total of 360 weanling pigs (DNA 200 x 400; initially 9.7 ± 0.23 kg BW) were used in a 21-d experiment with 6 pigs/pen and 10 replicate pens/treatment. Pigs were allotted to pens based on BW in a completely randomized block design to one of 6 diets: 1) Negative control (no organic acids or antibiotics); 2) Control + 0.25% Commercial Acidifier A) Control + 0.3% Commercial Acidifier B; 4) Control + 0.5% Commercial Acidifier C); 5) Control + 50 g/ton Carbadox; 6) Control + 400 g/ton Chlortetracycline). Dietary treatment had a significant impact (P < 0.05) on ADG, ADFI and G:F for the entire experiment. Carbadox negatively impacted ADG and ADFI (P < 0.0001), while pigs fed CTC had improved (P < 0.0001) ADG compared to all other treatments. In summary, CTC continues to be a valuable additive to enhance piglet health and subsequent performance in the nursery. Further investigation surrounding the efficacy of dietary acidifiers is warranted given inconclusive evidence in this study. Finally, 2 experiments were conducted to: 1) evaluate corn dried distiller’s grains with solubles (DDGS) vs. corn gluten feed (CGF) as alternatives for soybean meal (SBM); and 2) evaluate feeding DDGS and an ionophore on Boer goat growth performance and carcass characteristics. In Exp. 1, a total of 75 Boer-goat kids (26.9 ± 0.2 kg) were allotted to one of 5 dietary treatments: 1) Negative control (100% SBM, 0% DDGS and 0% CGF; 100SBM); 2) Positive control (100% DDGS, 0% CGF and 0% SBM 100DDGS); 3) 66% DDGS, 33% CGF and 0% SBM (66DDGS/33CGF); 4) 66% CGF, 33% DDGS and 0% SBM (33DDGS/66 CGF); and 5) 100% CGF, 0% DDGS and 0% SBM (0DDGS/100CGF). Dietary treatment did not impact (P ≤ 0.21) any of the measured growth response criteria. In Exp. 2, a total of 72 Boer-goat kids (21.7 ± 0.8 kg) were allotted in a completely randomized design. Dietary treatments were: 1) SBM/No Ionophore (SBM-NI); 2) SBM with Ionophore (SBM-I); 3) DDGS/No Ionophore (DDGS-NI); and 4) DDGS with Ionophore (DDGS-I). There were no significant protein source  ionophore interactions (P = 0.15) for any growth criteria. Goats fed the SBM-I diet had significantly increased (P = 0.04) ADG compared to goats fed DDGS-NI. Dietary treatments did not impact (P > 0.05) carcass characteristics. In both experiments, ingredient prices for tested ingredients dictated changes in diet cost, but no differences were observed across treatments for feed cost per goat and cost/kg of gain (P > 0.10). In summary, these data suggest that corn co-products can be economically included in Boer-goat diets, however their impact on growth performance is variable compared to that of soybean meal. Further research to evaluate the efficacy of both corn co-products and ionophores in goat diets is needed.
Keywords: Feed additives; Nursery pig; Meat goat; Growth performance